REKONSTRUKSI PERLINDUNGAN HUKUM KREDITUR KONKUREN DALAM SISTEM KEPAILITAN INDONESIA: TELAAH KEADILAN DISTRIBUTIF DAN KEPASTIAN HUKUM - Gilang Fitri Hermawan; Djoni Sumardi Gozali; Saprudin Saprudin (Al-Adl : Jurnal Hukum, 2026)
This study aims to examine the legal standing of concurrent creditors within the Indonesian bankruptcy regime and to formulate a reconstruction model of legal protection that is more equitable without undermining legal certainty and efficiency. Concurrent creditors have traditionally occupied the lowest tier of priority, subordinate to secured and preferred creditors, resulting in the frequent marginalization of their rights. Employing normative legal research with statutory, conceptual, and comparative approaches, this study finds that the normative configuration of Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UUK–PKPU) continues to place concurrent creditors in a weak and subordinated position. The practice of distributing bankruptcy estates further reveals the dominance of secured creditors, the expansion of preferential claims, limited transparency on the part of curators, and inconsistencies in judicial decisions, all of which undermine legal certainty and distributive justice for concurrent creditors. As a remedial measure, this study proposes a reconstruction of legal protection through the establishment of minimum rights for concurrent creditors, restrictions on secured creditors’ execution rights, reform of preferential mechanisms, enhancement of curator transparency, strengthening of judicial oversight, promotion of consistency in court decisions, and revision of the UUK–PKPU by incorporating best practices from bankruptcy systems in other jurisdictions. This reconstruction is expected to reinforce the position of concurrent creditors while simultaneously preserving legal certainty and efficiency within Indonesia’s bankruptcy law framework.